Coverage of Altruistic Work of Industrial Workers of Fergana Region during the Second World War on the Pages of Frontline Newspapers - Makhmudjanovna, Atabayeva Nigora (International Journal on Integrated Education, 2023)
In the article, the contribution of workers and employees of the industry of Fergana region to the great victory over fascism and Japanese militarism is highlighted in the letters, news and articles from frontline newspapers published in Uzbek language on the fronts of the Second World War.